2016
DOI: 10.1039/c6ra04660f
|View full text |Cite
|
Sign up to set email alerts
|

A novel three-stage treatment train for the remediation of trichloroethylene-contaminated groundwater

Abstract: This study used a novel three-stage treatment train that was composed of chemical oxidation, anaerobic bioremediation and a passive reactive barrier (PRB) to remediate trichloroethylene (TCE)-contaminated groundwater. Batch oxidation and biodegradation experiments and a continuous column study were used to evaluate the compatibility of different technologies and the feasibility of the removal of TCE by the treatment train. The results of batch experiments show that high concentrations of TCE (50 mg L À1 ) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, co-metabolic biodegradation of TCE under aerobic conditions is limited if no extra carbon source is added. 1,22,23 Because TCE contamination was first detected in 2006, the results indicate that natural attenuation mechanisms at this site did not decrease TCE concentrations to the groundwater control standard. Therefore, more active remediation technologies are required for this site.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…However, co-metabolic biodegradation of TCE under aerobic conditions is limited if no extra carbon source is added. 1,22,23 Because TCE contamination was first detected in 2006, the results indicate that natural attenuation mechanisms at this site did not decrease TCE concentrations to the groundwater control standard. Therefore, more active remediation technologies are required for this site.…”
Section: Resultsmentioning
confidence: 89%
“… 24 Decreases of 2.5 to 6.0 pH units caused by persulfate have been observed in aqueous and soil slurry systems. 1 In general, pH plays an important role in affecting the performance for the degradation of contaminants in persulfate systems. Hussain et al 24 found that acid conditions (pH 2.0 and pH 4.0) are favorable to the degradation of p -chloroaniline (PCA) in a zero-valent iron-activated persulfate system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations